Comparative Studies on Quality Changes of Air Blast and Plate Frozen Mackerel (Rastrelliger kanagurta) During Frozen Storage - T.K., Srinivasa Gopal; I.P., Lakshmisha; C.N., Ravishankar; Ninan, George (Fishery Technology, 2025)
Mackerel (Rastrelliger kanagurta Cuvier ) frozen in commercial plate and air blast freezers were studied to compare the quality changes during frozen storage (-180C)/ The frozen fish were sealed in polythene bags of food grade Linear Low Density Polyethylene (LLDPE), 120 gauge thick conforming to IS: 9845 - 1981) then packed in 5-ply corrugated fiberboard carton and were analyzed for changes in quality during storage at -180C. The moisture and protein content in air blast frozen samples were decreased (p<0.05) at the end. There were no significant difference (p>0.05) in PV of both the samples. TBA of air blast frozen samples showed an increasing trend (p<0.05) than plate frozen samples. There was an increasing trend in FFA in both the samples but were not significantly different (p>0.05). The TMA-N and TVB-N of both the samples showed an increasing trend but air blast frozen samples showed little higher values (p<0.05) than plate frozen samples. The total plate count decreased significantly (p<0.05) in both the samples. The samples frozen in plate freezer were established to be superior (p<0.05) compared to air blast freezer with regard to sensory attributes like appearance, odour etc., and overall acceptability. The present study indicated that plate frozen samples were slightly better than air blast frozen samples in quality because of quick freezing effect but mackerel frozen by both plate and air blast freezer were acceptable even after 3 months of storage at -18Â°C.